Fullerene C70–TiO2 hybrids with enhanced photocatalytic activity under visible light irradiation. Issue 42 (25th September 2015) - Wang, Shengyao; Liu, Changwei; Dai, Ke; Cai, Peng; Chen, Hao; Yang, Changjun; Huang, Qiaoyun
Abstract : Longer-lived photo-generated charge carriers and efficient visible light adsorption give rise to excellent visible-light-driven photoactivity of C70 –TiO2 hybrids. Abstract : Fullerene C70 modified TiO2 (C70 –TiO2 ) hybrids were fabricated through a hydrothermal method from titanium sulfate and functionalized C70 . The structures of the synthesized hybrids were characterized by X-ray diffraction, UV-vis diffuse reflectance spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, scanning electron microscopy, transmission electron microscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy, Brunauer–Emmett–Teller surface area measurements, matrix-assisted laser desorption/ionization-time of flight-mass spectrometry and photoluminescence spectroscopy. The experimental results indicated that the introduction of C70 slightly reduces the crystallite size of TiO2 while extending its adsorption edge to the visible light region. C70 dispersed on the surface of TiO2 nanoparticles with covalent bonding, which generated strong interactions between the functionalized C70 and TiO2 . The O2 ˙ −, ˙OH and h + are active species which were proved by the trapping experiment. The photocatalytic degradation efficiency of sulfathiazole over C70 –TiO2 hybrids is higher than that over pure TiO2, C60 –TiO2, and a mechanical mixture of C70 and TiO2 under visible light irradiation. The excellent visible light-induced activity is rationalized by the results of photoluminescence spectroscopy; i.e., the intensities of emissions from C70 –TiO2 hybrids were found to be weaker than those from pure TiO2 and C60 –TiO2 hybrid.